Civil project management - Milicz Ákos (Proceedings of the "Scientific Management" and Management Science Today International Scientific Conference, 2013)
The theme of my thesis is the achievements of the Hungarian domestic non-governmental organizations (foundations, associations, federations) of winning and realizing projects from the perspectives of tendering. Based on interviews I collected data at six, big tender consulting organizations, where I asked their opinion about the project management and the realization of the winning civil organizations. Their insight in this subject shows very well the readiness and knowledge of the organizations concerning gaining tendering funds and then utilizing them. The research was built on the methodology of qualitative data collection and processing. The analysis of the interviews made it possible to compare the theoretical foundations of project management with the experience of today’s Hungary, and we can do this all in a special organizational scale, the civil sector. It is especially interesting to examine the characteristics and the differences among the civil social organizations so as to see why and how they are different in their project management from the rest of this sector. The research results also direct attention to the gaps which should be eliminated for the later success of the non-governmental organizations, in implementing projects alone or in consortiums with the aim of improving social welfare.